Mucocutaneous Leishmaniasis due to Leishmania infantum Infection - Kai-Philipp Linse; Christian Bogdan; Holger A. Haenssle; Ferdinand Toberer (Medical Journals Sweden, 2022)
Abstract is missing (Short communcation)